SPEECH ACT ANALYSIS OF MAIN CHARACTER IN THE SUPER MARIO BROS MOVIE - Ravi Al Bany Halqi; Aliva Rosdiana (IKIP Siliwangi, 2024)
Understanding language meaning is crucial in communication. Speaker employs speech acts and interlocutors to do what they want to do using appropriate language and manner in particular context. This study is aimed at investigating speech acts and language functions employed by main character in the Super Mario Bros movie. The method used in this study is socio-pragmatic with qualitative descriptive approach. The relationship between main character and other characters are investigated to gain how language function implied in speech act through utterances. The data collection used involves watching movie, transcribing utterances, and identifying data. The steps to data analysis involves classifying, reducting data, and analyzing data. The result illustrates that there are 125 data of speech acts found in Super Mario Bros movie which involves 125 utterances contains 52 data of assertives (42%), 2 data of commissives (2%), 61 data of directives (48%), and 10 data of expressives (8%). The most dominant speech act found is directive speech act. It indicates that the tendency of asking questions and begging is frequently found since the main character in Mario Bros movie used to produce these utterances.